Learning to Save the World : Global Health Pedagogies and Fantasies of Transformation in Botswana - Brada, Betsey Behr, 1976- (Book collections on Project MUSE., 2023)
"Using data from southeastern Botswana, efforts to educate HIV-positive children about their treatment are contrasted with global health rotations for American medical students in order to demonstrate that 'global health' is not a set of problems or institutions, but rather an imaginative practice that hinges on a range of pedagogies"--